Ideology and pluralism: A German view - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2019)
As a social science, economics studies social interactions. What distinguishes it from other social science disciplines is, firstly, its focus on interactions involving the management of scarce resources and, secondly, its conception of itself as generating traceable, verifiable findings that are free of normative judgements but instead yield 'objective knowledge'. Some regard this methodological foundation of positivist fallibilism as the feature that makes economics the 'queen of the social sciences'. Others are critical of these core assumptions, which they believe have no place in a social science. Interestingly, both critiques and defences of economics often make reference to ideology: defenders claim that economics is as free of ideological bias as it is possible to be, while critics deny economics' status as a science and instead regard it as an 'ideology that serves to uphold power relations'. This article explores the relationship between ideology and economics with special reference to German academia, and asks whether a pluralist approach to economics could help to make the discipline less vulnerable to the charge of being ideological.
Keywords: A12; A13; B40; B50; 330; ideology; pluralism; monism; value freedom; methodology; ontology